Annual report 2016: CGIAR Research Program on Forests, Trees and Agroforestry - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2017)
CGIAR Research Program on Forests, Trees and Agroforestry 2016 Annual Report